A Study of the Relationship between Consumer Credit and Lifestyle Demographics of Consumers of Bangladesh - Rahman, Ataur (Indian Journal of Marketing, 2010)
Bangladesh is a developing country. A large size of the population of this country is coming up as middle class every year. They are in continuous race to elevate the standard of their living and quality of life. Demographic factors influence people to get the goods they need and want, when they need and want those most for building their lifestyle. For this reason, they need to possess basic necessities of life by paying the price at a time out of their savings (National Bank Bangladesh Ltd., 2006). They cannot save money at a time to buy essential household durables (like TV, fridge, furniture, sofa-set etc.) to upgrade their lifestyle as they have to fulfill their basic needs. In this situation, credit is necessary for them to buy household goods. But their economic condition is not suited to get micro credit; because micro credit is for poverty alleviation. They do not have other resources to get a mortgage loan. Considering the demand, popularity and profitably of the consumer credit scheme and to diversify the area of investment as well as to play a beneficial role for the increasing number of people of the country, most of the private banks in Bangladesh offer consumer credit for their valuable customers (Prime Bank Ltd., 2007). At first, Islami Bank Bangladesh Ltd. introduced a consumer credit in 1993 in Bangladesh (Islami Bank Bangladesh Ltd, 1994). It was followed by Prime Bank Ltd. and Social Investment Bank Ltd., all of which started their services in 1995. Soon, several other banks joined and today, 19 of the 48 commercial banks offer consumer credit services in Bangladesh (Bangladesh Bank, 2006).